Communication Behaviour of Forage Growing Farmers in Kandi Belt of Jammu Division - Shabnam Kundal, S.K. Kher, P.S. Slathia, Poonam Parihar and Vinod Gupta, (Indian Journal of Extension Education, 2018)
Awareness and knowledge about improved technologies in Agriculture and allied can be upgraded throughmany information sources. Different strata of farmers use different types of information sources as per theirsocioeconomic status. Some farmers perceive fellow farmers, radio, television and newspapers as the mainsource of agricultural information while some perceive mass media useful to great extent in increasingagricultural production. In order to know the facts, a study was conducted in Samba and Kathua districts ofJammu division. From each district, three blocks were selected purposively and the final sample size consistedof 144 forage growing farmers. The study revealed that 68.05 per cent of the farmers had medium level (score6-9) of information seeking behaviour. Only 9.70 per cent fall in high (score above 9) level of informationseeking behaviour. Majorities (83.33%) of the respondents were in contact with neighbors and input agencies‘sometimes’. There was no significant difference in the use of personal localite channels of the farmers in thetwo districts (Kathua and Samba). Junior Agriculture Extension officers were major source of information forabout 70.83 per cent of the farmers. Overall 91.66 per cent of the farmers had never participated in anydemonstration conducted by the development agencies. There was no significant difference in the use ofpersonal cosmopolite channels of the farmers in the two districts (Kathua and Samba) as far as informationseeking is concerned. Overall 72.91 per cent of the farmers in the two districts of Kathua and Samba watchT.V. always. However out of 105 respondents’ only five farmers watch agricultural programmes on T.V.always. Neighbours and Input agencies contributed equally (83.33%) each to the knowledge of forage growerin personal localite channels.